การมีส่วนร่วมการจัดระเบียบพื้นที่สาธารณะตามหลักสังคหวัตถุ 4 ของผู้ประกอบการในเขตเทศบาลเมืองร้อยเอ็ด อำเภอเมืองร้อยเอ็ด จังหวัดร้อยเอ็ด - แสงสุวอ, เก่ง; อาจวิชัย, เวชสุวรรณ (วารสารรัฐศาสตร์สาส์น มหาวิทยาลัยมหามกุฏราชวิทยาลัย(Online); Vol 2 No 2 (2566): July-December 2023, 2023)
บทความวิจัยนี้มีวัตถุประสงค์ 1) เพื่อศึกษาระดับการมีส่วนร่วมการจัดระเบียบพื้นที่สาธารณะตามหลักสังคหวัตถุ 4 ของผู้ประกอบการในเขตเทศบาลเมืองร้อยเอ็ด อำเภอเมืองร้อยเอ็ด จังหวัดร้อยเอ็ด 2) เพื่อศึกษาเปรียบเทียบการมีส่วนร่วมการจัดระเบียบพื้นที่สาธารณะตามหลักสังคหวัตถุ 4 ของผู้ประกอบการในเขตเทศบาลเมืองร้อยเอ็ด อำเภอเมืองร้อยเอ็ด จังหวัดร้อยเอ็ด โดยจำแนกตาม เพศ อายุ ระดับการศึกษา และรายได้ 3) เพื่อศึกษาข้อเสนอแนะการมีส่วนร่วมการจัดระเบียบพื้นที่สาธารณะตามหลักสังคหวัตถุ 4 ของผู้ประกอบการในเขตเทศบาลเมืองร้อยเอ็ด อำเภอเมืองร้อยเอ็ด จังหวัดร้อยเอ็ด กลุ่มตัวอย่าง ได้แก่ ผู้ประกอบการจำหน่ายสินค้าในที่หรือทางสาธารณะที่ได้ทำการขออนุญาตขึ้นทะเบียนและชำระค่าธรรมเนียมกับเทศบาลเมือง จำนวน 205 คน เครื่องมือที่ใช้ในการวิจัย ได้แก่ แบบสอบถาม มีค่าความเที่ยงตรงเชิงเนื้อหา ระหว่าง 0.67-1.00 ค่าอำนาจจำแนกระหว่าง .272-.755 และค่าความเชื่อมั่นทั้งฉบับ เท่ากับ 0.78 สถิติที่ใช้ในการวิเคราะห์ข้อมูล ได้แก่ ค่าความถี่ ร้อยละ ค่าเฉลี่ย ส่วนเบี่ยงเบนมาตรฐาน สถิติที่ใช้ในการทดสอบสมมติฐานโดยใช้ t-test และ F-test ผลการวิจัยพบว่า 1) การมีส่วนร่วมการจัดระเบียบพื้นที่สาธารณะตามหลักสังคหวัตถุ 4 ของผู้ประกอบการในเขตเทศบาลเมืองร้อยเอ็ด อำเภอเมืองร้อยเอ็ด จังหวัดร้อยเอ็ด โดยรวมอยู่ในระดับมากที่สุด 2) ผลการทดสอบสมมติฐาน ผู้ประกอบการที่มีเพศ อายุ ระดับการศึกษา และรายได้ ต่างกัน มีส่วนร่วมการจัดระเบียบพื้นที่สาธารณะ ตามหลักสังคหวัตถุ 4 ของผู้ประกอบการในเขตเทศบาลเมืองร้อยเอ็ด อำเภอเมืองร้อยเอ็ด จังหวัดร้อยเอ็ด โดยรวมและรายด้าน ไม่แตกต่างกัน  3) ผู้ประกอบการได้ให้ข้อเสนอแนะเกี่ยวกับการมีส่วนร่วมการจัดระเบียบพื้นที่สาธารณะตามหลักสังคหวัตถุ 4 ของผู้ประกอบการในเขตเทศบาลเมืองร้อยเอ็ด อำเภอเมืองร้อยเอ็ด จังหวัดร้อยเอ็ด ได้แก่ 1) ควรส่งเสริมการมีส่วนร่วมกับหน่วยงานรัฐในการเสนอแนวทางการจัดระเบียบพื้นที่สาธารณะ 2) ควรให้เจ้าหน้าที่รัฐใช้วาจาที่สุภาพเรียบร้อยกับผู้ประกอบการในการขอความร่วมมือปฏิบัติการจัดระเบียบพื้นที่สาธารณะเพื่อช่วยเหลือกันและกันกับผู้ประกอบการ 3) ควรให้ความร่วมมือและมีส่วนร่วมในการแบ่งปันผลประโยชน์ให้กับผู้ประกอบการรายอื่นเมื่อได้รับประโยชน์จากการจัดระเบียบพื้นที่สาธารณะ 4) ควรมีการประเมินการปฏิบัติการจัดระเบียบเรียบร้อยพื้นที่สาธารณะโดยไม่หวังประโยชน์ตอบแทนจากหน่วยงานรัฐ The objectives of research article were: 1) to study the level of participation in public space organization based on Four principles of Sangahavatthu of the entrepreneurs in Mueang Roi Et Municipality, Mueang Roi Et District, Roi Et Province 2) to compare the participation in public space organization based on Four principles of Sangahavatthu of the entrepreneurs in Mueang Roi Et Municipality, Mueang Roi Et District, Roi Et Province classified by gender, age, education level and income 3) to study the recommendations of participation in public space organization based on Four principles of Sangahavatthu of the entrepreneurs in Mueang Roi Et Municipality, Mueang Roi Et District, Roi Et Province. research. TThe sample group consisted of 205 entrepreneurs selling products in places or public ways who had applied for registration and payment of fees under Roi Et Municipality. The research instrument was the questionnaires with content validity between 0.67-1.00. The discrimination was .272 - .755 and the reliability was 0.78. The statistics used in data analysis were frequency, percentage, mean, standard deviation. The statistics used to test the hypothesis using t-test and F-test. The research found that: 1) The participation in public space organization based on Four principles of Sangahavatthu of the entrepreneurs in Mueang Roi Et Municipality, Mueang Roi Et District, Roi Et Province overall, it was at the highest level. 2) The results of the hypothesis test found that entrepreneurs with different genders, ages, education levels and incomes participated in organizing public spaces based on four principles of Sangahavatthu of the entrepreneurs in Mueang Roi Et Municipality, Mueang Roi Et District, Roi Et Province overall and aspect, were not difference. This was not in accordance with the assumptions of the research. 3) Recommendations of the entrepreneurs about the participation in public space organization based on Four Principles of Sangahavatthu Mueang Roi Et Municipality, Mueang Roi Et District, Roi Et Province: (1) Should promote participation with government agencies in proposing guidelines for organizing public spaces. (2) Government officials should be polite and courteous to entrepreneurs in asking for cooperation in organizing public space operations to help each other with entrepreneurs. (3) Should cooperate and participate in sharing benefits with other entrepreneurs when they benefiting from the organizing public space. (4) The practice of organizing public space operations should be assessed without expecting benefits from government agencies.